The Fiddler of Driskill Hill : Poems - Middleton, David, 1949- (Book collections on Project MUSE., 2013)
Rooted in personal and regional history, this book celebrates a particular place - and the universal human experience. While evoking distinctive Louisiana landscapes, both north and south, these poems address the great philosophical and theological questions of the ages. In the title poem, a mysterious fiddler climbs Driskill Hill - the highest point of elevation in Louisiana - under the cover of darkness to practice his craft: ""I sing what is and ought to be / And will until I die: // For that's what bow and strings are for, / To raise things up in song / Between The Fall and Paradise / And urge the world along."